Algorithm of diagnostics and surgical treatment of intervertebral disk hernias in lumbar and lumbosacral spine - Z. V. Koshkareva (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The purpose of the research is substantiation of the choice of optimal surgical treatment for intervertebral disc hernias basing on the complex examination of patients. The authors worked out and introduced into practical healthcare the diagnostic algorithm for intervertebral disc raptures and constrictive processes of the spinal canal and dural sack. The algorithm includes clinical neurologic examination, complete blood count and biochemical blood test, electroneuromyography, densitometry, standard and functional spinal radiography, weight-bearing radiography, MSCT, MR1, and multisection CT myelography. The analysis of the obtained data has given the authors the opportunity to establish precise indications for surgical treatment of intervertebral hernias depending on the localization of the rupture, its size, degree of compression of neural structures, and the volume of osteo-neural involvement. The work presents three methods of surgical treatment of intervertebral hernias, optimizing the outcomes of surgical interventions based on the conducted diagnostic algorithm. 425 patients with intervertebral hernias were operated in different ways: 149 people - by laser-mediated vaporization; 131 people - with the use of video-assisted endoneurosurgery; and 145 patients were treated by surgical decompression with minimally invasive reconstruction of spinal canal and dural sack. The suggested methods of surgical treatment of intervertebral raptures are substantiated and confirmed by the patents, innovative surgical techniques and proved to be highly efficient. The use of said methods allowed to achieve good and satisfactory outcomes in 89.5 % of cases.